Mouse mammary tumor virus infection accelerates mammary carcinogenesis in Wnt-1 transgenic mice by insertional activation of int-2/Fgf-3 and hst/Fgf-4. - Shackleford, G M (1993)
Transgenic mice carrying the Wnt-1 protooncogene modified for expression in mammary epithelial cells exhibit hyperplastic mammary glands and stochastically develop mammary carcinomas, suggesting that additional events are necessary for tumorigenesis. To induce such events and to identify the genes involved, we have infected Wnt-1 transgenic mice with mouse mammary tumor virus (MMTV), intending to insertionally activate, and thereby molecularly tag, cooperating protooncogenes. Infection of breeding female Wnt-1 transgenics decreased the average age at which tumors appeared from approximately 4 months to approximately 2.5 months and increased the average number of primary tumors per mouse from 1-2 to > 5. A smaller effect was observed in virgin females, and infection of transgenic males showed no significant effect on tumor latency. More than half of the tumors from the infected breeding group contained one or more newly acquired MMTV proviruses in a pattern suggesting that most cells in tumors arose from a single infected cell. Analyses of provirus-containing tumors for induced or altered expression of int-2/Fgf-3, hst/Fgf-4, int-3, and Wnt-3 showed activation of int-2 in 39% of tumors, hst in 3%, and both int-2 and hst in 3%. DNA analyses with probes for protooncogenes and MMTV confirmed that the activations resulted from proviral insertions. There was no evidence for proviral insertions at the int-3, Wnt-3, or Wnt-1 loci. These findings provide further evidence that fibroblast growth factors Int-2 and Hst can cooperate with Wnt-1, another secreted factor, in mammary tumorigenesis, and they illustrate the capacity of this system to identify cooperating oncogenes.